2016
DOI: 10.1186/s12936-016-1589-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing demand-side barriers to uptake of intermittent preventive treatment for malaria in pregnancy: a qualitative study in two regions of Uganda

Abstract: BackgroundTo prevent malaria infection during pregnancy in endemic areas in Africa, the World Health Organization recommends the administration of intermittent preventive treatment in pregnancy (IPTp) as part of the focused antenatal care package. However, IPTp uptake in most countries remains low despite generally high antenatal care coverage and increased efforts by governments to address known bottlenecks such as drug stock-outs. The study explored factors that continue to impede uptake of IPTp among women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 38 publications
4
40
0
Order By: Relevance
“…This is in agreement with our previously reported results in the study on IPTp-SP coverage among delivering women conducted in the same setting [17]. Similar studies conducted in Uganda and Mali also found that late and infrequent ANC attendance were important factors influencing poor uptake of IPTp-SP and other malaria preventive measures [23,24]. Therefore, barriers to early ANC seeking behaviour are extremely relevant to the understand and improve the factors that influence IPTp-SP coverage.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with our previously reported results in the study on IPTp-SP coverage among delivering women conducted in the same setting [17]. Similar studies conducted in Uganda and Mali also found that late and infrequent ANC attendance were important factors influencing poor uptake of IPTp-SP and other malaria preventive measures [23,24]. Therefore, barriers to early ANC seeking behaviour are extremely relevant to the understand and improve the factors that influence IPTp-SP coverage.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have reported a linkage between late and infrequent ANC attendance with pregnant women’s cultural beliefs. For example, reluctance to disclose their pregnancy early, the tendency to only starting to attend ANC when the tummy is visible, which in most of the cases happens after the fifth month and a trend to only seek help when sick [10,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Level of health facility where ANC was received was significantly related to uptake of IPTp-SP with those receiving ANC at lower level health facilities reporting lower uptake than those who received ANC at hospitals. This finding is in consonance with findings elsewhere which indicated that quality of basic maternal health services was poorer or absent in lower level facilities [26,27,51]. Poor uptake at this level of health facilities could possibly be due to non-adherence to protocols, stockouts of SP, overwhelming patient load and understaffing as reported [26,27].…”
Section: Discussionsupporting
confidence: 88%
“…To improve IPTp-SP coverage, there is a pertinent need for capacity building of health workers to address the supply side gaps. Additionally, the demand side gaps can be addressed through social behaviour change interventions including health education sessions at health facilities, media campaigns and community engagement during outreach activities at the community level in order to shape women's and community attitudes towards IPTp [26,27]. The findings showed that the factors associated with optimal uptake IPTp-SP in East-Central Uganda were religion, age, wealth status, level of health facility where ANC was received and place of delivery.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation